The morphological estimation of therapeutic effect of combined rectal cream under acute anal fissure - Zaychenko, Anna; Stakhorskaya, Marina; Laryanovska, Yulia; Faizullin, Alexandr (ScienceRise: Medical Science, 2017)
Aim – morphological estimation of the influence of the combined rectal cream on the clinical course of an acute complicated anal fissure. Materials and methods. The study of the treating effect of the combined rectal cream was realized on the model of an acute complicated anal fissure on 24 nonlinear white rats with the weight 200-240g. For assessing the effectiveness of the studied preparation, the morphological experiment of the sphincter apparatus of the rectum was realized at 12 day of the experiment. Results: It was established, that the use of the combined rectal cream in animals with an acute complicated anal fissure had an essential therapeutic effect: at 12 day the ulcerous defect of a mucosa was revealed only in 33,3 % of animals. Defects were essentially less by size than in animals from the control pathology group, their surface was more cleaned from the purulent-necrotic content, the ripening of the newly created tissue that replaces nectorically changed ones in the defect zone is faster. Microcirculation disorders and inflammation of tissues of this zone were essentially less in all animals. Signs of the muscular tone of the internal anal sphincter were essentially less, comparing with the group of the control pathology. The control preparation “Proctozan” was inferior by the intensity of the therapeutic effect to the studied one. Conclusions: The therapeutic effect of the combined rectal cream under conditions of an acute combined anal fissure was manifested as a decrease of inflammation signs, microcirculation disorders, signs of the internal anal sphincter hypertone. Thus, the received experimental data testify to the expedience of further deep researches of its therapeutic action